The Influence of Country of Origin and Product Knowledge on Purchase Intentions and Product Evaluation as Mediation Variables - Yusuf, Zulfan; Sarboini (Indonesian Journal Economic Review (IJER), 2021)
This study was done to examine the effect from the country of origin and knowledge of product on purchase intention and product evaluation as mediating variable (study at electronics product, Maspion at Banda Aceh), the respondents of this study is Banda Aceh's society (purposive sampling). Model analysis in this study is using path analysis. Based on the result of the analysis found that country of origin have an influence on purchase intention, knowledge of product have no influence on purchase intention, country of origin have an influence on product evaluation, knowledge of product have to influence on product evaluation, evaluation product have an influence on purchase intention, the effect from the country of origin to purchase intention mediated by product evaluation, and the knowledge of the product to purchase intention mediated by product evaluation.